Investigators' Efforts To Resolve Online Fraud Criminal Act At The Police Of The Special Region Of Yogyakarta - Setyawan, Christina Natalia Riesty; Martha, Aroma Elmina (LPPM Universitas PGRI Sumatera Barat, 2024)
This study discusses the theoretical perspective of optimizing criminal law in the efforts of investigators to resolve online fraud crimes. This type of research is empirical legal research. Data sources consist of primary data in the form of interviews and secondary data in the form of primary, secondary and tertiary legal materials. Methods of collecting data by interview and literature study. The results of this study are, first, the constraints experienced by investigators, namely the difficulty in tracing perpetrators will usually use fake identities, the difficulty of opening perpetrator accounts because there are bank bureaucratic agreements, the absence of a special unit handling cybercrime crime cases and the lack of DIY Polda investigators who have the ability to and experience in the field of ITE or Cybercrime, secondly, Efforts to solve it namely Providing counseling and mentorship to the community; block accounts of criminals; addition of police personnel; additional computer equipment.